2021
DOI: 10.1063/5.0040201
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic coherent perfect absorber and laser modes via the non-Hermitian dopant in the zero index metamaterials

Abstract: In this work, we propose a simple scheme to realize an acoustic coherent perfect absorber (CPA) and laser modes by embedding a non-Hermitian dopant in a zero index metamaterial. When the dopant is filled with a loss medium at a specific level, the sample can absorb the incident waves completely. On the other hand, when the dopant is filled with a gain medium, the sample can act as a laser oscillator to boost the incident waves. The theoretical derivation based on the scattering matrix and the numerical simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Our theory provides an accurate guidance for both cases. Especially, in the latter case, it is shown that a medium with purely imaginary permittivity and permeability of opposite signs can realize CPA-laser, i.e., simultaneous CPA and laser at the same frequency, which is consistent with previous results [64][65][66][67][68][69][70][71]. Our work aims to provide a unified picture to design the parameters of a homogenous metamaterial slab that functions as CPAs, lasers or their coexistence.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Our theory provides an accurate guidance for both cases. Especially, in the latter case, it is shown that a medium with purely imaginary permittivity and permeability of opposite signs can realize CPA-laser, i.e., simultaneous CPA and laser at the same frequency, which is consistent with previous results [64][65][66][67][68][69][70][71]. Our work aims to provide a unified picture to design the parameters of a homogenous metamaterial slab that functions as CPAs, lasers or their coexistence.…”
supporting
confidence: 87%
“…Metasurfaces which feature the P T -symmetry have also been designed to achieve CPA, laser or their coexistence. However, coherent perfect absorption and lasing can also emerge in configurations without P T -symmetry [62,63], as well as a unique type of zero-index medium with both gain and loss [64][65][66][67], the pseudopassive media [68] or complex conjugate media [69][70][71][72][73], etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the PT-symmetric systems, the complex permittivity exhibits a symmetric spatial profile of ε(x) = ε * (−x) [25,26]. The scattering of electromagnetic waves by boundaries can produce CPA and laser effects [27]. When the amplitude and phase of the two incident waves are well-tuned (in-phase excitation), the outgoing waves will disappear, and the resulting may lead to perfect absorption.…”
Section: Introductionmentioning
confidence: 99%
“…After the extension from optics to acoustics, the progress in designing and realizing PT -symmetric acoustic systems has resulted in many nontrivial asymmetric effects such as unidirectional sound wave-vector manipulation, [31][32][33][34][35] unidirectional invisibility, [2,[36][37][38] and asymmetric reflection and diffraction. [39][40][41][42][43][44] Negative refraction as a special wave behavior has been realized by acoustic metamaterials where the effective density (𝜌) and bulk modulus (𝐵) are simultaneously negative. [45][46][47] It also enables new way of manipulating a sound field and plays an important role in a variety of applications, especially in acoustic focusing and imaging.…”
mentioning
confidence: 99%